Organization and management of the meteorological service in Poland - Radzka, Elżbeta; Jankowska, Jolanta; Król, Justyna (Management and Administration Journal, 2023)
Today, climate services are one of the most important tools for determining changes and adapting to climate change. In order to expand the existing climate information, members of the WMO and partner institutions from the United Nations Organization established a programme of a Global Framework for Climate Services-GFCS. In Poland, the principal and the parent institution engaged in meteorological and hydrological service is the Institute of Meteorology and Water Management - National Research Institute. Conducted in the IMWM-NRI National Hydrological and Meteorological Service includes the following subsystems: observation and measurement, ICT and communications, data processing, forecasting and warning. The institute continuously provides information to the state authorities and the public about the current state of the atmosphere and hydrosphere, as well as forecasts and warnings.